Analytically continued Fock space multireference coupled-cluster theory: application to the (2)Pi(g) shape resonance in e-N-2 scattering - Sajeev, Y; Santra, R; Pal, S (Journal of Chemical Physics, 2005)
The technique of Fock space multireference coupled-cluster (FSMRCC) is applied for the first time to the correlated calculation of the energy and width of a shape resonance in an electron-molecule collision. The procedure is based upon combining a complex absorbing potential with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigenvalue problem. The potential-energy curve of the (2)Pi(g) state of N-2(-) is calculated using the FSMRCC and multireference configuration-interaction (MRCI) level of theories. Comparison with the single-determinant Hartree-Fock theory indicates that correlation effects are important in determining the behavior of the resonance state. (C) 2005 American Institute of Physics.